An environmentally robust design of a high-speed pendulum-type laser vibrometer using an advanced position-sensitive detector for vibration frequency monitoring of tower-like structures. (February 2023) - Pham, Duy Hoa; Phan, Hoang Nam; Hoang, Phuong Hoa; Hoang, Le Phuong; Cao, Xuan Binh
Abstract: Vibration monitoring of tower-like structures is a major challenge in vibration-based structural health monitoring, which is commonly expensive and time-consuming. In this paper, a novel vibration frequency measurement system based on a classical pendulum and advanced optical instruments that provides rapid, high-precision vibration measurements is developed. This system is integrated by a laser-based pendulum with an ultrafast interface position detector to form a table-top vibrometer that can precisely monitor structural vibration frequencies. In which, the position of the laser beam spot on the position-sensitive detector produces a voltage signal that is continuously recorded as the pendulum oscillates around its equilibrium position. By a comparative study of vibration frequencies between shaking table tests on the proposed system and simulations, it can be concluded that the proposed measurement system is independent of friction on the rotation shaft and other resistances; this makes the system environmentally robust over the long-term use, and thus reduces significantly maintenance and labor costs, especially in the case of tower-like structures where the measurement point is difficult to human access.